2013
DOI: 10.1097/prs.0b013e31829fe35b
|View full text |Cite
|
Sign up to set email alerts
|

Sterile “Ready-to-Use” AlloDerm Decreases Postoperative Infectious Complications in Patients Undergoing Immediate Implant-Based Breast Reconstruction with Acellular Dermal Matrix

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 29 publications
1
80
3
Order By: Relevance
“…): key word searches included AlloDerm + cryopreserved + free-dried + sterile + ready-to-use], this is the second comparative study evaluating the complication rates between cryopreserved AlloDerm and its new ready-to-use version. 1 AlloDerm was first used in breast surgery in 2001 and its use in breast reconstruction was first published in 2005. 24 The original version of AlloDerm, cryopreserved AlloDerm, has been widely published.…”
Section: Discussionmentioning
confidence: 99%
“…): key word searches included AlloDerm + cryopreserved + free-dried + sterile + ready-to-use], this is the second comparative study evaluating the complication rates between cryopreserved AlloDerm and its new ready-to-use version. 1 AlloDerm was first used in breast surgery in 2001 and its use in breast reconstruction was first published in 2005. 24 The original version of AlloDerm, cryopreserved AlloDerm, has been widely published.…”
Section: Discussionmentioning
confidence: 99%
“…If a drain is hastily removed before drainage decreases adequately, seroma can occur [7,11,15,16]. Few studies have reported the exact removal time of the drain postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown no long-term differences in the physical properties of both types of ADM. 7 A recent study has demonstrated an overall parity of complication rates between RTU and total submuscular coverage of implants. 4 A prospective trial investigating sterile ADM found lowered infection and seroma rates with equivalent graft incorporation to aseptic ADM. 8 To date, a comprehensive analysis of etiology and risk factors for the development of red breast syndrome (RBS) has not been performed. Despite routinely meticulous sterile tissue, some patients experience idiopathic postoperative erythema, or RBS.…”
Section: Introductionmentioning
confidence: 99%
“…Increased morbidity, namely, infection, seroma, and flap necrosis, has been reported. 4 A meta-analysis showed that the use of ADMs may increase the odds of infection 5.37 times. 5 New products are introduced periodically, asserting improvements in efficiency, cost, and complication occurrence.…”
Section: Introductionmentioning
confidence: 99%